VD_FINDINFO Jug / 2024 / 430 vom 8. Oktober 2024 - VD Tribunal cantonal (2024)
ENLÈVEMENT D'ENFANTASPECTS CIVILS, REJET DE LA DEMANDE | 13 al. 1 let. a CLaH 80, 13 al. 1 let. b CLaH 80, 3 al. 1 CLaH 80